Development and Evaluation of the Chronic Time Pressure Inventory - Denovan, Andrew; Dagnall, Neil (Frontiers in Psychology, 2019)
The negative effects of chronic time pressure (i.e., time shortage and feelings of being rushed) are pervasive within modern society. Noting this, and the absence of an established self-report measure, the present paper developed and evaluated the Chronic Time Pressure Inventory (CTPI). Established theory informed the generation of items, resulting in an initial 15-item measure. Study 1, using parallel analysis, exploratory factor analysis and confirmatory factor analysis, examined CTPI factorial structure within a sample of 401 respondents. Additionally, reliability (omega and alpha) and convergent validity testing occurred by correlating the CTPI with the Perceived Stress Scale (PSS-10). Study 2 replicated the emergent, superior factor model in an independent sample of 163 respondents and assessed measurement invariance. Analysis further examined reliability (omega and alpha) and convergent validity. Across the two studies, results supported a bifactor solution, where a general overarching factor encompassed two discrete, but overlapping temporal factors (i.e., Feeling Harried and Cognitive Awareness of Time Shortage). Invariance testing indicated invariance of form, factor loadings, item intercepts and residuals across Study 1 and 2. The CTPI additionally demonstrated good omega and alpha reliability and satisfactory convergent validity with the PSS-10. Findings support Szollos’ (2009) theoretical conceptualisation of chronic time pressure and establish the CTPI as a psychometrically sound, theoretically aligned measure of the construct. Indeed, results advocate the CTPI as a promising instrument for conducting survey-based research into chronic time pressure.